Epigallocatechin-3-gallate Mo nanoparticles (EGM NPs) efficiently treat liver injury by strongly reducing oxidative stress, inflammation and endoplasmic reticulum stress - Yunrong Yang; Yunrong Yang; Min Liu; Min Liu; Tianjiao Zhao; Tianjiao Zhao; Qiaohui Chen; Qiaohui Chen; Yuqi Yang; Yuqi Yang; Shuya Wang; Shuya Wang; et al. (Frontiers Media S.A., 2022)
Drug-induced liver injury (DILI) is a serious clinical disease associated with reactive oxygen species (ROS) burst and subsequent inflammatory responses. However, traditional treatments were limited by low efficacy and serious side effects due to the special liver structure. Here, we developed a molybdenum (Mo)-based nanoparticles, EGM NPs, after overall consideration of the pathophysiology of DILI and the advantages of nanodrugs. It demonstrated that EGM NPs treated acetaminophen (APAP)-induced DILI by scavenging ROS and inhibiting inflammation. EGM NPs effectively scavenged various ROS and reduced cell apoptosis at the cellular level. More importantly, EGM NPs can treat APAP-induced DILI in vivo, reducing the levels of liver function indicators in mice with liver injury, scaling down the area of hepatocyte necrosis and successfully inhibiting endoplasmic reticulum (ER) stress in the liver. EGM NPs also showed a certain anti-inflammatory effect by reducing infiltration of macrophages, decreasing pro-inflammatory factors and inhibiting the expression levels of inducible nitric oxide synthase (NOS2) and myeloperoxidase (MPO). Collectively, our findings suggest that EGM NPs-based nanotherapeutic is a novel strategy for the treatment of DILI.